Building the Virtual World: A Literature Review on the Integration of Metaverse and Blockchain Technology - I Gede Iwan Sudipa; Putu Wirayudi Aditama; Christina Purnama Yanti (Sean Institute, 2024)
The present study explores the incorporation of blockchain technology within the metaverse, uncovering the potential for mutually beneficial outcomes that may revolutionise virtual environments, transaction security, and digital interaction. This study examines the recent advancements, obstacles, and uses of integrating blockchain and metaverse technologies through a literature review. It emphasises the critical role that AR/VR technology plays in the creation of immersive experiences. The findings indicate that the integration of blockchain technology and the metaverse presents a viable avenue towards enhanced virtual experiences that are interactive, decentralised, and secure. This has far-reaching implications across various sectors, including education, entertainment, culture, healthcare, and more. This study highlights the significance of additional progress and interdisciplinary cooperation in order to fully exploit the capabilities of this integrated digital ecosystem.